Studi Etnobotani Pemanfaatan Tanaman Sayuran di Kabupaten Pamekasan - Setiawan, Eko (Rekayasa, 2017)
Indigenous vegetables have become popular, but the information of crops cultivated by farmers is limited. The objective of this research was to investigate the crops cultural of indigenous vegetables by farmers and their uses in Pamekasan district, East Java, Indonesia during rainy season, December of 2016. In depth observations of the indigenous vegetables and interviews with farmers were conducted in six sub-districts, i.e., Pasean (50 m above the sea level; asl), Waru (159 m asl), Pakong (250 m asl), Kadur (140 m asl), Pademawu (7 m asl) and Tlanakan (22 m asl). This study showed that utilization of the indigenous vegetables in Pamekasan district is still varied and not yet maximal. Vegetable crop has been highest utilities by the society in Waru Sub-district (50%), Tlanakan Sub-district (47.1%) and Pademawu Sub-district (42.1%), while the vegetables utilization has not been maximal in Kecamatan Kadur (53.3%), Pakong Sub-district and Pasean Sub-district (50%). The most un-utilities vegetables are in Kecamatan Pakong (22.2%) and Pasean sub-districts (20%).